PENGEMBANGAN PENGOLAHAN JAGUNG DAN UBI KAYU UNTUK MENINGKATKAN PENDAPATAN PETANI DI KABUPATEN TUBAN - Anam, Choirul (Universitas Islam Darul Ulum, 2009)
The potency of corn and cassava in Tuban was respectively 3.026.937 kwintal in 2008 and 1.277.291 kwintal, where most of them was sold as fresh product, and only little was prepared as processed food. The development of corn and cassava processing was one of Â first alternative problem solving and potency of optimalization of corn and cassava in Tuban Regency. The use method was observation Â in four districts at corn and cassava production centre in Tuban.Â Districts Tuban, Montong, Plumpang and Palang. Secundary data in Tuban. Activities of processing found in Tuban were fried corn, cassava flour chip, fermented cooking and cassava chip. It has not been the cultivation of cassava materials. It has not also been the cultivation of tortilla and corn. To increase the farmers income, it needs product cultivation of corn and cassava with the suitable prices and capacities for households.